Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/ange.201509278
|View full text |Cite
|
Sign up to set email alerts
|

Capsule–Capsule Conversion by Guest Encapsulation

Abstract: Guest-induced M 18 L 6 -M 24 L 8 capsule-capsule conversion is reported. Both capsules are composed of Pd II ethylenediamine units (M) and 1,3,5-tris(3,5-pyrimidyl)pyrimidine (L), and form trigonal bipyramidal (M 18 L 6 )a nd octahedral (M 24 L 8 )c losed-shell structures with huge hydrophobic inner spaces.T he M 18 L 6 trigonal bipyramid is converted to the M 24 L 8 octahedron through encapsulation of large aromatic guests,w ith the latter capsule possessing ac avity volume three times larger than the former.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…193 Molecular cages have been also used to achieve nanomechanical processes, and recently, control of the shape and size of the molecular cavity by an external imput has been reported in both covalent and self-assembled cages. 194,195 In this context it was demonstrated that dynamic motion can be induced with hemicryptophane 46 from fully folded to extended states by coordination/decoordination of the metal ion ( Figure 26). 62 Indeed, stereoisomers of hemicryptohane 46 present "imploded" conformations in solution as evidenced by NMR spectroscopy and in the X-ray crystal structure of M-(R,R,R)-(R,R,R)-46.…”
Section: Molecular Breathingmentioning
confidence: 98%
“…193 Molecular cages have been also used to achieve nanomechanical processes, and recently, control of the shape and size of the molecular cavity by an external imput has been reported in both covalent and self-assembled cages. 194,195 In this context it was demonstrated that dynamic motion can be induced with hemicryptophane 46 from fully folded to extended states by coordination/decoordination of the metal ion ( Figure 26). 62 Indeed, stereoisomers of hemicryptohane 46 present "imploded" conformations in solution as evidenced by NMR spectroscopy and in the X-ray crystal structure of M-(R,R,R)-(R,R,R)-46.…”
Section: Molecular Breathingmentioning
confidence: 98%
“…15b ). 128 Extending the backbone of their previous ligand to form tritopic, W-shaped 160, Pd II 3 160 4 double cage 161 was isolated. The binding ability of the new cage was initially investigated with C 60 , which had previously been encapsulated in the cavity of the Pd II 2 L 4 single-cage analogue 156.…”
Section: Transformations Induced By External Stimulimentioning
confidence: 99%
“…A) Assembly of the "molecular ship-in-a-bottle" cage complexes 12 and 13 from the empty Fe/Zn cube 10,and ametallated tetrapyridine porphyrin 11.B )Schematic representation of the size-selective transformations catalysedb ythe "molecular ship-in-a-bottle" cage 12. [54] Angewandte Chemie Reviews octahedral M 24 L 8 cage, [87] as well as the transformation between an octahedral M 20 L 8 cage and bowl-shaped M 8 L 4 cage. [88] Last year the Nitschke group reported am ore subtle example where anion binding induced the transformation of one tetrahedral Fe 4 L 4 cage into an isomeric tetrahedral Fe 4 L 4 cage ( Figure 8).…”
Section: Guest-induced Host Transformationmentioning
confidence: 99%